Impact of Maternal Melatonin Suppression on Amount and Functionality of Brown Adipose Tissue (BAT) in the Newborn Sheep - Seron-Ferre, Maria; Reynolds, Henry; Mendez, Natalia Andrea; Mondaca, Mauricio; Valenzuela, Francisco; Ebensperger, Renato; Valenzuela, Guillermo J.; Herrera, Emilio A.; Llanos, Anibal J.; Torres-Farfan, Claudia (Frontiers in Endocrinology, 2015)
In human and sheep newborns, brown adipose tissue (BAT) accrued during fetal development is used for newborn thermogenesis. Here we explored the role of maternal melatonin during gestation on the amount and functionality of BAT in the neonate. We studied BAT from 6 lambs gestated by ewes exposed to constant light from 63% gestation until delivery to suppress melatonin (LL), 6 lambs gestated by ewes exposed to LL but receiving daily oral melatonin (12mg at 1700 hrs, LL+Mel) and another 6 control lambs gestated by ewes maintained in 12h light:12h dark (LD). Lambs were in-strumented at 2 days of age. At 4-6 days of age, they were exposed to 24ºC (thermal neutrality condi-tions) for 1 hr, 4ºC for 1 hr and 24ºC for 1 hr. Afterward, lambs were euthanized and BAT was dissected for mRNA measurement, histology and ex vivo experiments. LL newborns had lower central BAT and skin temperature under thermal neutrality and at 4°C, and higher plasma norepinephrine concentration than LD newborns. In response to 4°C, they had a pronounced decrease in skin temperature and did not increase plasma glycerol. BAT weight in LL newborns was about half of that of LD newborns. Ex vivo, BAT from LL newborns showed increased basal lipolysis and did not respond to NE. In addition, expression of adipogenic/thermogenic genes (UCP1, ADBR3, PPARγ, PPARα, PGC1α, C/EBPβ, and perilipin) and of the clock genes Bmal1, Clock and Per2 was increased. Remarkably, the effects observed in LL newborns were absent in LL+Mel newborns. Thus, our results support that maternal melatonin during gestation is important in determining amount and normal functionality of BAT in the neonate.